(3efGXQI Hjf GdSja hGdejRGfs - (3eMeO Hf Ydj UOQ GdTQjYIs
(3ChdgG (B:s
(3HYO GdMeO MeOkG jVjb Yf JbOjQg GdejRGf hYdi fHjg fHi GdSja UdGg Hcd efgG Sjha GdCdSfI hHYO adeG CfRd Gddg GdejRGf djLQi Hg GdbSW Hjf GdfGS hGdMOjO GdLRjd GdefGaY hTOjO GdHCS s
(3BNQgG (B:s
(3aEfc Ef QaYJ bOQi HbSWGS YOdc hYdi eNdUjI NGUg JeJ HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B15s
(3GdfSNI HgG MhGTs
(3HBNQgG fbhd eNJdaI JUhas
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs